Examining the Experiences of Young Adults Who Were Traumatized via Social Media After the Maraş Earthquake: A Phenomenological Research - Meral, Şeyda; Çuhadar, Betül; Karanalbant, İmren; Baykal, Nur Başer (Ankara University, 2025)
The earthquake that struck Kahramanmaraş on February 6, 2023, and affected many provinces in Türkiye, also had a negative impact on individuals who did not experience it directly, largely due to the rapid flow of information on social media. This study aims to explore the experiences of young people who were exposed to earthquake-related content on social media after the Kahramanmaraş earthquake. For this purpose, 12 participants who had not directly experienced the earthquake were selected. To identify these individuals, the Secondary Traumatic Stress Scale for Social Media Users was administered to 140 people aged between 18 and 26, and those with the highest scores were invited to participate. The participants shared their post-earthquake social media experiences through semi-structured interviews and described the changes they observed in themselves after viewing traumatic content. The interview transcripts were analyzed using MAXQDA-24. The analysis revealed three main themes: impacts, coping, and recommendations. The impacts theme was categorized into psychological, physical, behavioral, and cognitive responses. The coping theme included seeking and providing social support, raising awareness, and individual coping strategies. Finally, the recommendations theme focused on avoiding sensitive content in posts and promoting more functional sharing. The findings were interpreted in light of the existing literature in the discussion and conclusion sections. © 2025, Ankara University. All rights reserved.
Maraş Depremi Sonrasında Sosyal Medya Üzerinden İkincil Travma Geliştiren Genç Yetişkinlerin Deneyimlerinin İncelenmesi: Bir Fenomenoloji Araştırması
Keywords: Earthquake; Qualitative Research; Secondary Trauma; Social Media